An assesment on the three worlds theories of Karl Popper and Jurgen Habermas - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2015)
In this study, it is aimed to outline three world theories of Karl Popper and Jurgen Habermas comparatively. In this context, it is also aimed to assess Habermas' critics as positivist to Karl Popper who is an opponent to positivism inside it and his abstraction on the three world theory under the influence of Karl Popper. The differences between their opinions stem from their main arguments about the methodology of natural and social sciences.
Keywords: Popper; Habermas; Three world theory; Communicative theory; Metodology